Severe Neurologic Impairment in Mice with Targeted Disruption of the Electrogenic Sodium Bicarbonate Cotransporter NBCe2 (Slc4a5 Gene) - Kao, Liyo (American Society for Biochemistry and Molecular Biology, 2011)
The choroid plexus lining the four ventricles in the brain is where the majority of cerebrospinal fluid (CSF) is produced. The secretory function of the choroid plexus is mediated by specific transport systems that allow the directional flux of nutrients and ions into the CSF and the removal of toxins. Normal CSF dynamics and chemistry ensure that the environment for neural function is optimal. Here, we report that targeted disruption of the Slc4a5 gene encoding the electrogenic sodium bicarbonate cotransporter NBCe2 results in significant remodeling of choroid plexus epithelial cells, including abnormal mitochondrial distribution, cytoskeletal protein expression, and ion transporter polarity. These changes are accompanied by very significant abnormalities in intracerebral ventricle volume, intracranial pressure, and CSF electrolyte levels. The Slc4a5(−/−) mice are significantly more resistant to induction of seizure behavior than wild-type controls. In the retina of Slc4a5(−/−) mice, loss of photoreceptors, ganglion cells, and retinal detachment results in visual impairment assessed by abnormal electroretinogram waveforms. Our findings are the first demonstration of the fundamental importance of NBCe2 in the biology of the nervous system.